2020
DOI: 10.1002/ps.5786
|View full text |Cite
|
Sign up to set email alerts
|

Host plant odours and their recognition by the odourant‐binding proteins of Diaphorina citri Kuwayama (Hemiptera: Psyllidae)

Abstract: BACKGROUND: The Asian citrus psyllid (ACP), Diaphorina citri, is one of the major pests in citrus production because it transmits huanglongbing, a devastating disease of citrus plants. Odourant-binding proteins (OBPs) play an important role in the olfactory perception of insects. Revealing the function of DcitOBPs is beneficial to the development of new ACP management strategies.RESULTS: An analysis of the components of volatiles from the new shoots of six host plant species showed that ⊎-caryophyllene was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Multiple strategies may be applied, such as the application of specific VOCs to attract or repel insects, or the dysfunction of OBPs through the key binding sites of VOCs. These universal strategies may be useful in attempts to manage the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Psyllidae), which prefers to lay eggs on young citrus leaves and is the vector of Candidatus Liberibacter asiaticus causing Huanglongbing 73,74 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple strategies may be applied, such as the application of specific VOCs to attract or repel insects, or the dysfunction of OBPs through the key binding sites of VOCs. These universal strategies may be useful in attempts to manage the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Psyllidae), which prefers to lay eggs on young citrus leaves and is the vector of Candidatus Liberibacter asiaticus causing Huanglongbing 73,74 …”
Section: Discussionmentioning
confidence: 99%
“…These universal strategies may be useful in attempts to manage the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Psyllidae), which prefers to lay eggs on young citrus leaves and is the vector of Candidatus Liberibacter asiaticus causing Huanglongbing. 73,74…”
Section: Wileyonlinelibrarycom/journal/psmentioning
confidence: 99%
“…The tissue‐specific expression patterns of OBP‐encoding genes in insects are usually related to their physiological functions 26 . OBP6 exhibited high expression in the antennae of D. citri and stronger binding affinity to some host plant volatiles 25,26 . Our previous studies have shown that AbamOBP1, AbamOBP24, and AbamOBP30, have evident male antenna‐specific expression patterns 40 .…”
Section: Discussionmentioning
confidence: 99%
“…OBP14 in Cnaphalocrocis medinalis Güenée (Lepidoptera: Pyralidae) was found to mediate the recognition ability for nerolidol and β‐ionone 24 . Some OBPs in Diaphorina citri are involved in the perception of some important host plant odorants such as β‐caryophyllene and some terpenoids 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…There are many methods and devices that have been reported to extract and analyze VOCs in plant leaves, such as simultaneous distillation–extraction (SDE) [ 20 ], steam distillation (SD) [ 21 ], and supercritical fluid extraction (SFE) [ 22 ]. Wang et al analyzed the components of volatiles from the new shoots of six healthy host plant species via the headspace solid-phase microextraction (HS-SPME) method and showed that β-caryophyllene was the characteristic VOC in flushing shoots of the tested ACP host plant species [ 23 ]. However, they did not analyze VOCs from HLB-infected species.…”
Section: Introductionmentioning
confidence: 99%